THE INFLUENCE OF INTERNAL CONTROL SYSTEMS ON EMPLOYEE PERFORMANCE IN STATE-OWNED CONSTRUCTION COMPANIES IN INDONESIA - Rangga Bagus Sena; Ayu Chairina Laksmi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
BUMN construction companies in Indonesia are experiencing declining performance. Management is crucial to help improve performance by focusing more on internal control to ensure the company achieves its goals. The objective of this study was to analyze the influence of the Control Environment, Risk Assessment, Monitoring Activities, Control Activities, Information and Communication, and Monitoring on employee performance. The research method used quantitative research. The population in this study was all employees of state-owned construction companies in Indonesia, with a sample size of 150 employees. Data collection methods used a questionnaire with a Likert scale. Data analysis methods included multiple linear regression analysis, the Classical Assumption Test, the t-test, the F-test, and the R-test. The results of the study indicate that the Control Environment has a significant positive effect on employee performance, with a t-test significance value of 0.000